2019
DOI: 10.1177/1533317519872635
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Conducting Nonpharmacological Interventions to Manage Dementia Symptoms in Community-Dwelling Older Adults: A Cluster Randomized Controlled Trial

Abstract: This study assessed the feasibility of conducting 3 nonpharmacological interventions with older adults in dementia, exploring the effects of chair yoga (CY), compared to music intervention (MI) and chair-based exercise (CBE) in this population. Using a cluster randomized controlled trial (RCT), 3 community sites were randomly assigned 1:1:1 to CY, MI, or CBE. Participants attended twice-weekly 45-minute sessions for 12 weeks. Thirty-one participants were enrolled; 27 safely completed the interventions and fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 43 publications
3
76
1
Order By: Relevance
“…23–31 In the remaining 12 studies, 4 did not find significant differences between groups after treatment (3 studies compared yoga with an inactive control group and 1 compared it with acceptance and commitment therapy). 3237 The other eight studies found a significant difference between groups after treatment on at least one subscale or summary score. 2235 When yoga was compared to no intervention, the results were generally in favour of the yoga group, only one study found results in favour of the control group (subscales ‘sleep’ and ‘outlook’).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…23–31 In the remaining 12 studies, 4 did not find significant differences between groups after treatment (3 studies compared yoga with an inactive control group and 1 compared it with acceptance and commitment therapy). 3237 The other eight studies found a significant difference between groups after treatment on at least one subscale or summary score. 2235 When yoga was compared to no intervention, the results were generally in favour of the yoga group, only one study found results in favour of the control group (subscales ‘sleep’ and ‘outlook’).…”
Section: Resultsmentioning
confidence: 97%
“…3237 The other eight studies found a significant difference between groups after treatment on at least one subscale or summary score. 2235 When yoga was compared to no intervention, the results were generally in favour of the yoga group, only one study found results in favour of the control group (subscales ‘sleep’ and ‘outlook’). 28 When yoga was compared to another active intervention, there was generally no significant difference between groups, only one study found results in favour of the yoga group, 29 and one study found some subscales in favour of the active control group (subscales ‘pain’ and ‘health perception’) and another sub-score in favour of yoga (subscale ‘cognition’).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The results for the effects of active music making and anxiety were unclear. Five studies measured anxiety, and two 28,40 found a positive effects, one small (d = À0.12), one large (d = À1.71). The two studies by Giovagnoli et al utilized the same music protocol (using Improvisation), so more diverse protocol utilizing active music-making activities are needed to understand music's effect on anxiety.…”
Section: Discussionmentioning
confidence: 97%